2018
DOI: 10.1042/bsr20171184
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of GABAB receptor activation on spatial cognitive function and hippocampal neurones in rat models of type 2 diabetes mellitus

Abstract: The present study was conducted with the aim being to investigate the effect γ-aminobutyric acid type B (GABAB) receptor activation have on spatial cognitive function and hippocampal neurones found in the rat models of type 2 diabetes mellitus (T2DM). T2DM rat models were then established, randomized, and subsequently assigned into normal control (NC), T2DM, T2DM + chemical grade propylene (CGP), T2DM + baclofen, and T2DM + CGP + baclofen groups. T2DM rats’ weight and blood sugar concentrations were monitored.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 29 publications
(29 reference statements)
1
12
0
Order By: Relevance
“…Meanwhile, TEM observations showed that CA1 neuronal ultrastructures were impaired in DM rats, manifested by accumulation of APs, damaged mitochondria, and decreased organelles. These findings are in line with previous studies that hippocampal neuronal loss and structure impairment may cause the cognitive deficits in DM animals . Interestingly, our results implied that autophagic flux blockage in the CA1 hippocampus may be responsible for structure damage to this region and impairment of cognitive function in DM rats, which indicated by the evidences that CQ worsened the CA1 injury and cognitive function decline, while RAP ameliorated the CA1 impairment and cognitive function deficits in DM rats.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Meanwhile, TEM observations showed that CA1 neuronal ultrastructures were impaired in DM rats, manifested by accumulation of APs, damaged mitochondria, and decreased organelles. These findings are in line with previous studies that hippocampal neuronal loss and structure impairment may cause the cognitive deficits in DM animals . Interestingly, our results implied that autophagic flux blockage in the CA1 hippocampus may be responsible for structure damage to this region and impairment of cognitive function in DM rats, which indicated by the evidences that CQ worsened the CA1 injury and cognitive function decline, while RAP ameliorated the CA1 impairment and cognitive function deficits in DM rats.…”
Section: Discussionsupporting
confidence: 93%
“…Accumulating evidences have confirmed that DM is a major pathogenesis factor for cognitive deficits . Curcumin has been shown to be an effective agent for attenuating diabetic encephalopathy and improving surgery‐induced cognitive dysfunction in mice .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have revealed that diabetes leads to the pathogenesis of other co‐morbidities, such as cardiovascular disease, kidney disease, and peripheral nerve disease . Diabetes has also been associated with increased neuronal damage, particular altered structure and function in the hippocampus, a brain region responsible for learning and memory . Gu et al (2019) assessed the effect of nicotinate‐curcumin, a novel curcumin derivate, on streptozotocin‐induced diabetic rats.…”
Section: Protective Actions Of Curcuminmentioning
confidence: 99%